2021
DOI: 10.1037/ocp0000280
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for improving psychological detachment from work: A meta-analysis.

Abstract: Psychological detachment from work during off-job time is crucial to sustaining employee health and wellbeing. However, this can be difficult to achieve, particularly when job stress is high and recovery is most needed. Boosting detachment from work is therefore of interest to many employees and organizations, and over the last decade numerous interventions have been developed and evaluated. The aim of this metaanalysis was to review and statistically synthesize the state of research on interventions designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 87 publications
(208 reference statements)
6
99
1
8
Order By: Relevance
“…Our results showed the benefits of the recovery experiences during off-job time as a moderator of organizational arrangements. These results support the positive interaction between work and non-work factors and open avenues for designing interventions to enrich this interaction [81,82]. However, different recovery experiences suggest different outcomes depending on the situation.…”
Section: Managerial Implicationssupporting
confidence: 69%
“…Our results showed the benefits of the recovery experiences during off-job time as a moderator of organizational arrangements. These results support the positive interaction between work and non-work factors and open avenues for designing interventions to enrich this interaction [81,82]. However, different recovery experiences suggest different outcomes depending on the situation.…”
Section: Managerial Implicationssupporting
confidence: 69%
“…Intervention research focusing on workrelated thoughts is so far relatively limited (for a review Karabinski et al, 2021;Lohmann-Haislah et al, 2019;Verbeek et al, 2019;Wendsche et al, 2018aWendsche et al, , 2020. Of the various types of work-related thoughts, detachment and positive work reflection have been most frequently addressed in intervention studies.…”
Section: Interventions Focusing On Work-related Thoughtsmentioning
confidence: 99%
“…Interventions could be developed that teach people to actively utilize different strategies to either suppress work-related thoughts or to shape their thoughts into functional thoughts (see Karabinski et al, 2021 for a first review of detachment interventions). These individual-level interventions could then be complemented with organizational-level interventions that support functional ways to think about or forget about one's work during off-job time.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…. Karabinski and colleagues [41] recently reviewed the literature on such interventions. They found that workdirected interventions aiming to reduce job demands have largely not been investigated so far and that average effect sizes are rather low (d = 0.14).…”
Section: Practical Implicationsmentioning
confidence: 99%